Analysis of e-learning implementation in adult learning (andragogy) - Indah Namira Sari; Dinn Wahyudin; R. Rusman (Inovasi Kurikulum, 2024)
E-learning has relevance to be applied to adult learning as independent learners. This research aims to analyze the effectiveness of e-learning in adult learning (andragogy). In the context of adult learning based on continuous e-learning, there are significant changes in the objectives and content of teaching, social roles, forms, and nature of communication between teachers and students, based on e-learning. The research method uses a literature study of 77 articles found and analyzed based on the steps used. The research results showed that articles regarding e-learning in adult learning were found on the topics "learning outcomes" in higher education, "implementation according to plan" in job training institutions, "application in work practice" in job training institutions, satisfaction, and efficiency. Based on these results, it can also be seen that measuring the effectiveness of e-learning in adult learning mostly uses quantitative and qualitative methods. Meanwhile, although the mixed method exists, it is not as big as the other two methods. Then, the factors supporting the effectiveness of e-learning in adult learning were found in the number of selected articles, namely those related to the quality of teachers/students/lecturers, infrastructure, quality of teaching materials, and quality of learning strategies.